6 - L’obtention du crédit bancaire par les PME au Cameroun - Kenfack, Mireille Koumetio (Africa Development, 2021)
This article highlights a new problematic issue on variables that explain the process for obtaining a bank loan in developing countries. The purpose is to explain the access of company managers to bank loans by setting social variables as catalysts. Using a convenience sample of 93 companies and a positivist interpretation, obtaining a bank loan is determined by factors including the manager’s commitment to the confidentiality of company information, the manager’s commitment to independence of their company, the perceived uncertainty from the environment, the manager’s share capital, the manager’s adherence and commitment to social networks, trust and close identity relationship between the manager and bankers. The outcomes of analyses reveal that only 11.8 per cent of companies have a high indebtedness, compared to 61.3 per cent of companies holding very little debts. The outcomes also highlight two types of behaviors with a dualist effect on the possibility for companies to obtain bank loans, namely: organizational behavior in terms of commitment to information confidentiality and company independence, exercising a depressive and therefore negative effect on this possibility of obtaining bank loans; and the manager’s societal/relational behavior – materialized by their share capital, networking and trust – that exercises a progressive and therefore positive effect on the same possibility of obtaining bank financing. Their activation by the manager makes it more effective than others in obtaining the required funds for their development, their growth and their survival. In short, this research helps to understand that, besides company characteristics and economic and financial factors, obtaining a bank loan by the company manager is also explained through their organizational and societal behavior.